2022
DOI: 10.1590/fst.10122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heating method and refrigerating time on nutritional quality and digestive characteristics of refrigerated Chinese steamed bread

Abstract: Two re-heating methods and different refrigerating time were carried to compare the re-heating stored, refrigerated bread quality. Compared with the natural thawed steamed, sensory properties of re-heating bread were significantly improved, steam method improved moisture content while that re-heated by microwave decreased, the secondary structure of protein was significantly affected by re-heating. Rapidly digestible starch (RDS) content in bread re-heated by steam and by microwave decreased significantly, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Fourier transform infrared spectroscopy (FTIR) determination could reflect protein molecular interactions and protein structure changes (Muadiad & Sirivongpaisal, 2022). The amide I region (1 600 -1 700 cm -1 ), including α-helix (1 650 -1 660 cm -1 ), β-sheet (1 600 -1 640 cm -1 ), β-turn (1 660 -1 700 cm -1 ), and random coil (1 640 -1 650 cm -1 ) were used to analyze the secondary structure of proteins (Gao et al, 2019;Xie et al, 2022a). The protein secondary structure of the two processing methods was shown in Figure 5a and Figure 5b.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%
“…Fourier transform infrared spectroscopy (FTIR) determination could reflect protein molecular interactions and protein structure changes (Muadiad & Sirivongpaisal, 2022). The amide I region (1 600 -1 700 cm -1 ), including α-helix (1 650 -1 660 cm -1 ), β-sheet (1 600 -1 640 cm -1 ), β-turn (1 660 -1 700 cm -1 ), and random coil (1 640 -1 650 cm -1 ) were used to analyze the secondary structure of proteins (Gao et al, 2019;Xie et al, 2022a). The protein secondary structure of the two processing methods was shown in Figure 5a and Figure 5b.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir) Analysismentioning
confidence: 99%
“…The steamed bread developed by MTBF-WF dough (W MTBF = 0, 10, 20, 30, 40, and 50%) were prepared according to a published method (Xie et al, 2022). First, 1.0 g dry yeast was dissolved in 38 °C water and set aside.…”
Section: Preparation Of Steamed Breadmentioning
confidence: 99%
“…The CSB quality was investigated using evaluation method described by Xie et al (2022), the evaluate standard was showed in Table 1. The sensory evaluation was performed by 8 trained panelists who major in food science and technology, and the average value obtained from them was regarded as the last result.…”
Section: Sensory Evaluation Of Steamed Breadmentioning
confidence: 99%